Análisis a los estados financieros en la Cooperativa de Ahorro y Crédito “CACPE Célica” del cantón Célica, periodo 2020 – 2021 - Torres Gonza, Ximena Alejandra (2023)
The Curricular Integration Work constitutes a contribution to the Savings and Credit Cooperative "CACPE Celica" on the economic and financial structure. The general objective is to apply the Financial Analysis to the Savings and Credit Cooperative "CACPE Celica", period 2020 -2021 to examine the development in the management of resources. The methodological approach is based on a mixed type research, quantitative-qualitative, because it provides contextualized orientation and valuation of the financial structure; using methods such as: scientific, deductive, inductive, analytical, synthetic, mathematical and statistical, which allowed collecting bibliographic information by means of principles, laws, rules, norms, establishing a logical order of the particular aspects to carry out the study of the results obtained through calculations and graphs and writing the final report, the research techniques such as observation and bibliographic review, allowed identifying the insufficiencies in the management of financial resources, so that managers know the real situation of the entity of which they are in charge. The results allowed the fulfillment of the proposed objectives, the vertical analysis allowed to know the level of participation of each account within the statements, determining the composition and structure of the same, being the Loan Portfolio the account with the highest representation with 80.73% in 2020 and 80.01% in the year 2020, and 80.01% in the year 2020. With the horizontal analysis, the existing variations of its Assets, Liabilities and Equity were known, demonstrating a sustainable growth in the periods of study. Likewise, several indicators established by the Superintendence of Popular and Solidarity Economy (SEPS) were applied, identifying the accounts that need to be addressed. Subsequently, a financial report was prepared detailing the results of the analyses performed. It is concluded that, the results presented allowed to know the financial structure of the entity, this will allow to implement policies and strategies that are successful in areas that contribute to the successful management of the entity allowing it to remain within the financial market.